2001
DOI: 10.3109/2000-1967-165
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical decompression without laminectomy in lumbar spinal stenosis

Abstract: Our objectives were to study a/ the clinical results of microsurgical decompression without laminectomy compared to those reported from standard decompression laminectomy in patients with central lumbar spinal stenosis, and b/ if the microsurgical technique could prevent post-operative instability and concomitant symptoms.Twenty-one patients were treated, 11 men and 10 women, aged 47-81 years. Fourteen patients had "pure" stenosis whereas 7 had additional diseases that compounded the symptoms of stenosis. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…3,9,11,22,26,[30][31][32][33]38,42 In our study, the 8.6% incidence of reoperation for residual or restenosis at operated levels and recurrent disc herniation were close to or lower than the average of values reported in the literature. 9,12,15,30,32,37,42 Palmer et al 33 in their prospective clinical series of 8 patients, utilized the surgical microscope and tubular retractor system in microscopic fenestration for lumbar spinal stenosis reported only one durotomy (12.5%) that was covered with Gelfoam. In our study, there were no serious complications such as nerve root injury, cauda equina syndrome, spondylodiscitis, or deep vein thrombosis.…”
Section: A a B Bsupporting
confidence: 69%
See 1 more Smart Citation
“…3,9,11,22,26,[30][31][32][33]38,42 In our study, the 8.6% incidence of reoperation for residual or restenosis at operated levels and recurrent disc herniation were close to or lower than the average of values reported in the literature. 9,12,15,30,32,37,42 Palmer et al 33 in their prospective clinical series of 8 patients, utilized the surgical microscope and tubular retractor system in microscopic fenestration for lumbar spinal stenosis reported only one durotomy (12.5%) that was covered with Gelfoam. In our study, there were no serious complications such as nerve root injury, cauda equina syndrome, spondylodiscitis, or deep vein thrombosis.…”
Section: A a B Bsupporting
confidence: 69%
“…16,18,19,41 Getty et al 10 in 1981, introduced conventional open unilateral and bilateral laminotomy for decompression of LCS as a less invasive surgical option with comparable results reported since then and ranging from 59% to 84% improvement rates. 2,29,30,34,42 Only few series 35,37,41 have directly compared open laminotomy with open laminectomy. Several studies 1,2,20,22,31,33,38 have shown benefits of spinal endoscopic fenestration, including decreased blood loss, shorter operative time, shorter hospital duration, decreased postoperative narcotic requirement, decreased rate of infection and CSF leak, and a decrease in time required for returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…In patients without preoperative spondylolisthesis, a rate of progressive postoperative spondylolisthesis up to 31% and, in patients with preoperative olisthesis, an incidence of progressive slipping after surgery that is even higher, varying from 30 to 100% has been reported (6,9,12,18,20,24,29). In 2.0% of the patients in the present series, resurgery for spinal fusion became necessary.…”
Section: Postoperative Instabilitymentioning
confidence: 49%
“…After a mean follow-up period of 2.25 years, 84% of 50 patients showed good postoperative results. In a prospective study of 21 patients, Nyström et al(20) observed good outcome in 66% of patients at a mean duration of 2.25 years after surgery. Comparable results with 59 to 91% improvement rates after laminotomy were described by other authors during mean follow-up periods of up to 5.5 years(1-3, 7, 14, 15, 17, 18, 26, 35).…”
mentioning
confidence: 97%
“…The incidence of ULBD complications varies among reports. Dural tears are a very common complication, occurring in approximately 6.8%–18% of open surgeries and tubular procedures ( 22 , 33 , 34 ) and 0%–7.2% of endoscopic ULBD procedures ( 11 , 19 , 25 ). The reason for this difference is that clear surgical visualization and careful operation under endoscopy help prevent dural tears in the narrow surgical space where high-speed drills and osteotomes are used.…”
Section: Discussionmentioning
confidence: 99%